Human DC3 Antigen Presenting Dendritic Cells From Induced Pluripotent Stem Cells - Satoh, Taiki; Toledo, Marcelo A. S.; Boehnke, Janik; Olschok, Kathrin; Flosdorf, Niclas; Götz, Katrin; Küstermann, Caroline; Sontag, Stephanie; Seré, Kristin; Koschmieder, Steffen; Brümmendorf, Tim H.; Chatain, Nicolas; et al. (Frontiers in Cell and Developmental Biology, 2021)
Dendritic cells (DC) are professional antigen-presenting cells that develop from hematopoietic stem cells. Different DC subsets exist based on ontogeny, location and function, including the recently identified proinflammatory DC3 subset. DC3 have the prominent activity to polarize CD8+ T cells into CD8+ CD103+ tissue resident T cells. Here we describe human DC3 differentiated from induced pluripotent stem cells (iPS cells). iPS cell-derived DC3 have the gene expression and surface marker make-up of blood DC3 and polarize CD8+ T cells into CD8+ CD103+ tissue-resident memory T cells in vitro. To test the impact of malignant JAK2 V617F mutation on DC3, we differentiated patient-specific iPS cells with JAK2 V617Fhet and JAK2 V617Fhom mutations into JAK2 V617Fhet and JAK2 V617Fhom DC3. The JAK2 V617F mutation enhanced DC3 production and caused a bias towards erythrocytes and megakaryocytes. The patient-specific iPS cell-derived DC3 are expected to allow studying DC3 in human diseases and developing novel therapeutics.